(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This study analyzes the map-making method developed by Ptolemy in the elaboration of his Geographia. The aim of this analysis is to reveal and define the locating system used by the author in order to place the inland towns of the Iberian Peninsula. After a critical examination of the dif-ferent possible systems, the study shows their potential use for the location of the cities in the Iter ab Asturica per Cantabriam Caesaraugustam (known as the 27th itinerary) by comparing the distances deduced from the Ptolemaic coordinates with those transmited by the Antonine Itinerary. The results prove that Ptolemy used a two-phase locating process: first, he calculated arithmetically the positions of towns with astronomical data; next, according to them and by means of a graphical system he located the cities that only had geometric data.